Workshops to Disseminate the Canadian Thoracic Society Guidelines for Chronic Obstructive Pulmonary Disease to Health Care Professionals in Ontario: Impact on Knowledge, Perceived Health Care Practices and Participant Satisfaction - Dilshad Moosa; Maria Blouin; Kylie Hill; Roger Goldstein (Canadian Respiratory Journal)
BACKGROUND: The Canadian Thoracic Society (CTS) has developed a clinical practice guideline (CPG) regarding the management of patients with chronic obstructive pulmonary disease (COPD). Implementation of this CPG in the primary care setting requires an effective dissemination strategy.